The Role of Thyroid Diseases and their Medications in Cardiovascular Disorders: A Review of the Literature - Omidi, Negar; Khorgami, Mohammadrafie; Tajrishi, Farbod Z.; Seyedhoseinpour, Amirhosein; Pasbakhsh, Parichehr (Current Cardiology Reviews, 2020)
The association between thyroid disease and cardiovascular manifestations is significant and undeniable. Previous studies have explained several aspects of the effects of thyroid hormone on the heart and cardiovascular system. Accordingly, both hyper and hypothyroidism can cause important alterations in cardiac rhythm, output and contractility as well as vascular resistance and blood pressure. Since treating the thyroid abnormality, especially in its initial stages, could lead to a significant improvement in most of its resultant cardiovascular disturbances, early suspicion and recognition of thyroid dysfunction, is necessary in patients with cardiovascular manifestations. In this in-depth review, we discuss the physiological roles as well as the effects of abnormal levels of thyroid hormones on the cardiovascular system. We also review the effects of the medications used for the treatment of hyper and hypothyroidism on cardiac function. In the end, we discuss the association between thyroid function and amiodarone, an effective and frequently-used antiarrhythmic drug, because of its well-known effects on the thyroid.
Keywords: hypothyroidism